Beach narrowing on prograding coasts: Examples from the tropics to subtropics of eastern Australia - Cowley, D.; Harris, D.L.; Moss, P.T.; Shulmeister, J. (Geomorphology (Amsterdam, Netherlands), 2022)
Subtropical to tropical sandy beaches are subject to a wide variety of processes that influence shoreline position, though they receive little research attention compared to temperate coastlines. This presents challenges to understanding the drivers of long-term coastal change, particularly in places like the sub/tropical margins of Australia, where there are significant differences in local to regional geologic, oceanographic, and climatic conditions. Here, we investigate changes in beach planform morphology for a number of beaches in Queensland, Australia, over a period of up to 90 years using high resolution (0.5–5 m pixel size) aerial photographs. In total, 945 images were orthorectified and bounding features for the subaerial beach (high water and dune vegetation lines) were digitised to extract shoreline change statistics for 15 beaches ranging from the tropics to subtropics, between 15°S and 28°S. Three beach types were identified, defined based on lateral boundary features and the scale of shoreline/beach width variability. These include low variability beaches with two bounding rocky headlands (type 1); beaches with one headland and one river boundary, with the most significant shoreline adjustment away from the headland (type 2); and highly variable beaches with two river boundaries (type 3). Our change analysis demonstrates overall seaward displacement of the high water and vegetation lines, but also net losses in beach width due to fast rates of seaward vegetation advance in a tropical setting. These changes are largely consistent along this coastline, despite differences in exposure to deep-water waves and large variation in tidal ranges. Long-term accretion persists here despite rising sea levels over the past century. This result suggests a long-term net positive sediment budget along this section of the coast that is likely a reflection of global adjustments to tropical climate, and associated increases in terrestrial sediment generation and dune vegetation growth rates. Overall, this study provides insights into a variety of coastal settings through the subtropics and tropics and highlights the importance of tracking change along both the landward and seaward edges of the subaerial beach, regardless of exposure and associated wave regimes. •Tropical beach width declines while shorelines advance seaward.•Dune vegetation cover has increased, reducing the size of subaerial beaches.•Variability in beach width is drastically higher on beaches bound by rivers.•Alongshore supply of fluvial sediment dominates in low wave energy tropical areas.•Data-driven analyses provide more detailed insights into decadal coastal change.